Punicalagin suppresses methicillin resistance of Staphylococcus aureus to oxacillin - Su-Hyun Mun; Ok-Hwa Kang; Ryong Kong; Tian Zhou; Sang-A. Kim; Dong-Won Shin; Dong-Yeul Kwon (Elsevier, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is an important human pathogen that is cross-resistant to most β-lactam antibiotics. We investigated whether oxacillin, which is a β-lactam antibiotic, alone or in combination with punicalagin can affect the penicillin binding protein 2a (PBP2a)-mediated resistance of MRSA. Susceptibility testing of punicalagin with oxacillin was performed using the microdilution and checkerboard assay and the growth curve assay. Binding affinity of punicalagin for cell wall peptidoglycan (PGN) was confirmed by an increased concentration of PGN in bacterial cultures containing punicalagin. The level of PBP2a was analyzed by western blotting. Punicalagin exhibited antimicrobial activity in the viability assay and increased the susceptibility of MRSA to oxacillin. PGN interfered with the antimicrobial activity of punicalagin and prevented the synergistic activity of punicalagin and oxacillin. Increasing the concentration of punicalagin and maintaining a constant concentration of oxacillin resulted in synergistic suppression of the expression of the mec operon (mecA, mecI, and mecR1). The production of PBP2a was suppressed by the addition of punicalagin to oxacillin. Our findings demonstrate that punicalagin potentiates the effect of oxacillin on MRSA by reducing the transcription of mecA (a gene marker for methicillin resistance), which resulted in a reduced level of PBP2a. Keywords: MRSA, Punicalagin, PBP2a, β-lactam, Synergistic